Psicologização da queixa escolar: o que pensam os professores sobre “aluno problema”? - Cedro, Aline (2021)
The research consulted 76 teachers of the municipal network of primary schools of the city of Arujá in the state of São Paulo, 71 of whom answered a questionnaire and 5 answered the interview guided by semi-structured script, this, in order to access teaching beliefs which motivate practices of referring the “problem student” to health professionals and, above all, to psi professionals. The introduction will offer a historical overview of the participation of European scientists in the process of validating intelligence tests and other influences of these in the initial format of the Brazilian school, in addition to presenting the first forms of assistance aimed at families of difficult students. Subsequent, and luz de Freitas (2012); Lima (2018); Patto (2015); Mantovaninni (2001); Carvalho (2000); and Cury (2002), cultural and scientific convictions will be presented towards understanding the child's level of intelligence in the learning process, tending towards stigmatization. The inspiration in the Theory of Social Representations (TSR) will approach the process of constitution of knowledge through common sense and the formation of the structure of knowledge thus bringing together the procedural and structural approach in TRS that, according to Moliner and Guimelli (2015), the classification is theoretical, however, in different types of research, the approaches are combined. (JOCHEVCLOVITCH, 2008; JODELET, 2001, 2014, 2017; ABRIC, 2001, MOSCOVICI, 2017; SÁ, 1996, 1998; SPINK, 1993). The information produced through field research was systematized and later processed using computational statistics of similarity analysis, prototypical analysis and word cloud, using the Iramuteq software. The results obtained revealed that, for the investigated teachers, the term family is associated with behavioral disorder and, consequently, the non-apprehension of school contents by students considered to be problematic. Thus, it became evident that the belief focused on about 90 years ago remains active in the participants' repertoire.